2017
DOI: 10.15252/emmm.201708193
|View full text |Cite
|
Sign up to set email alerts
|

Compounds producing an effective combinatorial regimen for disruption of HIV ‐1 latency

Abstract: Highly active antiretroviral therapy (HAART) has improved the outlook for the HIV epidemic, but does not provide a cure. The proposed “shock‐and‐kill” strategy is directed at inducing latent HIV reservoirs, which may then be purged via boosted immune response or targeting infected cells. We describe five novel compounds that are capable of reversing HIV latency without affecting the general T‐cell activation state. The new compounds exhibit synergy for reactivation of latent provirus with other latency‐reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…The LRAs MMQO, AV6, 57704, and PH03 were identified in four separate screens, but carry a common central quinoline structure, which we propose may represent a privileged structural motif. In chemical biology and medicinal chemistry, privileged structures are represented by a semirigid molecular scaffold that when modified by multiple hydrophobic residues or functional groups produce versatile binding properties that confer the capacity to interact with diverse biochemical targets .…”
Section: Lras With a Common Privileged Structure Affect Various Targetsmentioning
confidence: 87%
See 2 more Smart Citations
“…The LRAs MMQO, AV6, 57704, and PH03 were identified in four separate screens, but carry a common central quinoline structure, which we propose may represent a privileged structural motif. In chemical biology and medicinal chemistry, privileged structures are represented by a semirigid molecular scaffold that when modified by multiple hydrophobic residues or functional groups produce versatile binding properties that confer the capacity to interact with diverse biochemical targets .…”
Section: Lras With a Common Privileged Structure Affect Various Targetsmentioning
confidence: 87%
“…Identification of novel compounds with HIV latency reversing activity is a relatively young endeavor; we describe results from 18 small molecule screens, but only two of which have involved extensive unbiased libraries of 100K compounds or more (Table ) . Considering that 100s of HTP screens involving very large libraries have been focused toward identification of novel cancer drugs over the past 20 years, efforts toward identification of novel HIV LRAs by comparable strategies appear to be in their infancy.…”
Section: Chemical Biology Of Hiv Provirus Lrasmentioning
confidence: 99%
See 1 more Smart Citation
“…A short course of treatment with ingenol mebutate gel (US Food and Drug Administration-approved [FDA-approved] Picato) leads to effective clearance of AK lesions (1,2,6). We and others have previously shown that ingenol mebutate can reactivate latent HIV in the primary CD4 + T cells of HIV-infected patients under suppressive ART (7)(8)(9)(10)(11). Several families of compounds with PKC agonist activity can induce latent HIV expression by activating the PKC/NF-κB signaling pathway (12), but many of them have also been associated with systemic toxicities in animal studies (12).…”
Section: Introductionmentioning
confidence: 99%
“…single agents, nevertheless the response seems modest for potential clinical use [20][21][22]. While the possibility of more potent candidates or combinations is perceivable, rationale suggests that most, if not all of these molecules induce clinical toxicity because of their dissemination into and thereby activation of bystander cells that do not harbor the virus.…”
mentioning
confidence: 99%